O uso de dobraduras como recurso para o estudo de conceitos geométricos - GLOWECKI, Kenia Carla Belo Domingues (2015)
This work aims to present mathematics activities ideas from use with folds as an alternative to learning, exploration and expansion of basic concepts related to geometric shapes, angles, flats, vertices, likeness, proportionality notions of algebra, allowing students not only rational and conceptual acquisition, as well as the development of own skills and competencies for mathematical thinking. The emphasis of the work is the study of geometric elements, as mankind has always sought to understand and explain the world around you, unlock the natural phenomena and to discover the relationships between them. To do so, resorted to drawings, measurements and annotations, which favored the emergence of geometry. The proposals were developed in the school, Escola de Referência em Ensino Médio Oliveira Lima, with students of the three years of High School, and consisted of three stages: Diagnosis, implementation and evaluation of results. The activities not only contributed to the development of geometrical thinking of students from interactions with objects, maturing of inductive and deductive thinking, but also favored the development of relational and personal skills of cooperation, interaction, engagement, attention, communication and autonomy.